World public sector report 2005 : unlocking the human potential for public sector performance. (United Nations, Dept. of Economic and Social Affairs, 2005)
The conditions of globalization, including economic integration, fiscal discipline, introduction of information communications technologies and democratic governance, have increasingly forced states to redefine their role in public management and to reform the public administration system. However, there is growing realization among decision makers that policy and institutional reform per se will not be sufficient to revitalize the public sector. Major strengthening of the knowledge, skills, values, attitudes and leadership abilities of human capital is also needed to transform the public sector, particularly in developing countries and countries with economies in transition. This year's report is expected to contribute to global and national debates on this topic.--Publisher's description.